Profile of women with mental illness admitted in shelter care homes; a co-relational description of changing sociocultural scenario in India - Febna Moorkath; Mysore Narasimha Vranda; Channaveerachari Naveenkumar (Wolters Kluwer Medknow Publications, 2020)
Background: The prevalent explanations of gender and mental illness in the Indian social structure often highlighted in terms of traditions and gender-colored norms which is confirmed with the patriarchal framework. The combination of women and diagnosis of mental illness disturbs the prescribed gender expectations which accelerate the family abandonment, and many women lead their life in shelter care homes after psychiatric hospitalization. The aim of the study is to assess the sociodemographic characteristics of the residents admitted in shelter care homes and understand the co-relational aspects of changing sociocultural scenario. Subjects and Methods: Recruited 50 women residents living in 14 centers both the governmental and nongovernmental shelter care homes in Bengaluru, Karnataka. Utilized sociodemographic datasheet to assess the sociodemographic variables and retrospective file review to elicit commonalities among the sample. Results: The current study reveals that majority (74%) belongs to the nuclear family, lived in a rented house before institutionalization (46%). The reason for stay in shelter care home reported to be family abandonment and rejection (72%) and majority of the residents experiencing chronic homelessness (92%) are unmarried/separated (82%) and majority revealed none of the family members ever visited them in shelter care homes (66%). Conclusion: It is imperative to understand the connection between sociodemographic details of the women admitted in shelter care homes and the rapid changes occurring in the sociocultural structure for comprehensive understanding of mental illness-homelessness-institutionalization nexus.